Phenotypic and genetic analysis of carcass quality of different breeds’ fatlings - LUKAC, D; VIDOVIC, V; INIC, N D; TOMOVIC, V (The Indian Journal of Animal Sciences, 2016)
Dissection and quantitative-genetic analysis of carcass quality was performed on 318 fatlings of 5 different pig breeds: German, Dutch and Belgian Landrace, Yorkshire and Hampshire. Significant fixed effects (sex and genotype) and regression effects (age and body weight at slaughter) were fitted in the statistical model. Genetic parameters were estimated using the restricted maximum likelihood (REML) procedure based on an animal model with multivariate analyses. Heritability estimates for carcass traits were moderate to high except for back weight and neck weight. Among most of the carcass quality traits, the midrange strong and very strong positive genetic and phenotypic correlations were established. The traits that were analyzed showed sufficient genetic variation, indicating that their improvement is possible through genetic selection. Genetic variability was stable and expressed and justified further genetic changes in the desired direction.